CCL7 contributes to the TNF‐alpha‐dependent inflammation of lesional psoriatic skin. Issue 7 (4th May 2015) - Brunner, Patrick M.; Glitzner, Elisabeth; Reininger, Baerbel; Klein, Irene; Stary, Georg; Mildner, Michael; Uhrin, Pavel; Sibilia, Maria; Stingl, Georg
Abstract Chemokines are small chemotactic proteins that have a crucial role in leukocyte recruitment into tissue. Targeting these mediators has been suggested as a potential therapeutic option in inflammatory skin diseases such as psoriasis. Using quantitative RT‐PCR, we found CCL7, a chemokine ligand known to interact with multiple C‐C chemokine receptors, to be markedly increased in lesional psoriasis as opposed to atopic dermatitis, lichen planus, non‐lesional psoriatic and normal control skin. Surprisingly, this increase in CCL7 mRNA expression exceeded that of all other chemokines investigated, and keratinocytes and dermal blood endothelial cells were identified as its likely cellular sources. In an imiquimod‐induced psoriasis‐like mouse model, CCL7 had a profound impact on myeloid cell inflammation as well as on the upregulation of key pro‐psoriatic cytokines such as CCL20, IL‐12p40 and IL‐17C, while its blockade led to an increase in the antipsoriatic cytokine IL‐4. In humans receiving the TNF‐α‐blocker infliximab, CCL7 was downregulated in lesional psoriatic skin already within 16 hours after a single intravenous infusion. These data suggest that CCL7 acts as a driver of TNF‐α‐dependent Th1/Th17‐mediated inflammation in lesional psoriatic skin.